Factors affecting the intention to purchase foreign products (imported products) : a study from Bangladeshi consumers perspective - Chowdhury, Naila Anwar (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2013)
In today's globally connected marketplace, dramatic increase in cross border trade and distribution of products beyond national boundaries have undoubtedly widened the availability of foreign products across the world at large. Therefore, in order to survive in this modern, competitive marketplace it has become important to understand what affects the intention of purchasing foreign products of consumers from different countries. Taking this into account, the research at hand has been crafted with the ultimate objective of unveiling the factors that are affecting consumers' intention of buying foreign products, giving special attention to Bangladeshi consumers. In order to do so, this study has greatly relied on the framework that has been derived from prior literature. In addition, for this empirical study data had been collected through the employment of a self-structured questionnaire from a total of 260 (n=260) Bangladeshi consumers residing in the two major cities of the country, Dhaka and Chittagong, as these cities have the widest availability of foreign products. The data collected from the respective respondents have been analyzed through the means of Statistical Package for Social Sciences (SPSS) and Analysis of Moment Structure (AMOS) software. At the initial stage, statistical analyses, particularly Descriptive Analysis as well as Exploratory Factor Analysis (EFA) were conducted through SPSS, after which Measurement Model and Structural Equation Modeling (SEM) were run by using AMOS. Findings have demonstrated that, in accordance to prior studies, brand image and quality of foreign product carry significant positive effects on purchasing intention, and on the other hand religiosity leaves a significant negative effect on purchase intention of foreign products. Furthermore, findings have also disclosed that country of origin image carries a significant positive effect on brand image and ethnocentrism carries a negative effect on quality of foreign product in purchase intention of foreign products. The findings derived from the study will facilitate marketers in the creation of effective marketing strategies, and at the same time they will also be valuable to academicians as well as consumers at large.